Designing a Science Based Strategy to Prepare for the Next Pandemic - Hou, Antong; Asmis, Reto; Crowder, Mark (Journal of Student Research, 2022)
Since late 2019, the COVID-19 pandemic has ravaged countries and peoples across the globe. As of August 27, 2021, 215 million people have been infected. Most countries have utilized different responses, which significantly influenced the impact of the disease on their respective populations. In this paper, we used an investigative approach to identify the proper measures needed to prepare for the next pandemic. Various National COVID-19 response strategies were identified and compared. In addition, scientific findings of the characteristics of the COVID-19 virus were utilized to identify appropriate responses. It was found that measures including swift lockdowns, border closings, and travel restrictions, accompanied by mask-wearing, mass testing, contact tracing, and healthcare system adjustments were key pieces of pandemic response. In addition, virology research, equipment stockpiling, manufacturing plans, healthcare worker benefits, and healthcare re-education are key to be prepared in advance. These findings are crucial in ensuring that the world is adequately prepared for the next pandemic.